Delayed phospholamban phosphorylation in post-conditioned heart favours Ca2+ normalization and contributes to protection. (27th June 2014) - Inserte, Javier; Hernando, Víctor; Ruiz-Meana, Marisol; Poncelas-Nozal, Marcos; Fernández, Celia; Agulló, Luis; Sartorio, Carmem; Vilardosa, Úrsula; Garcia-Dorado, David
Abstract: Aims: It has been shown that sarcoplasmic reticulum calcium ATPase (SERCA) plays a critical role in reperfusion injury. Moreover, ischaemic post-conditioning (PoCo) results in protein kinase G (PKG) activation which has been proposed to modulate phospholamban (PLB) and SERCA. We assessed whether PLB phosphorylation contributes to the cardioprotective effects of PoCo. Methods and results: Isolated Sprague–Dawley rat hearts were submitted to 40 min of ischaemia and reperfusion with and without a PoCo protocol that reduced infarct size by 48%. Reperfusion caused a rapid phosphorylation in PLB at Ser16 and Thr17 that was delayed by PoCo. NO-independent activation of soluble guanylate cyclase (sGC) (ataciguat) and cAMP-dependent protein kinase (PKA) inhibition (KT5720) mimicked the reduction in Ser16 phosphorylation in reperfused control hearts, while in PoCo hearts the inhibitors of PKG (KT5823) and phosphodiesterase 2 (BAY-60-7550) reverted it. CaMKII activity measured by Thr287 phosphorylation was reduced in PoCo. In reperfused control hearts, inhibition of PLB phosphorylation or SERCA (thapsigargin) simulated the cardioprotective effects of PoCo. Ataciguat reduced cytosolic Ca 2+ oscillations and improved Ca 2+ recovery in cardiomyocytes subjected to anoxia–reoxygenation and infarct size by 32% in rats with 30 min of the left anterior descending coronary artery occlusion and 2 h of reperfusion. Blockade of Na + /Ca 2+ -exchanger (NCX; KB-R7943) impaired Ca 2+ control in cardiomyocytes and abolished cardioprotection in PoCo hearts. Conclusions: PoCo reduces SERCA activity at the onset of reperfusion by delaying PLB phosphorylation through activation of PKG and inhibition of PKA and CaMKII. This effect contributes to PoCo protection by favouring cytosolic Ca 2+ extrusion through NCX, and it may be mimicked by pharmacological stimulation of sGC.